Effects of resistance training on preventing muscle atrophy and bone loss in simulated weightless population: a systematic review and meta-analysis - Chen, Aona; Guo, Chenggen; Zhou, Yingcong (Frontiers in Physiology, 2025)
ObjectiveThis systematic review and meta-analysis examined the effects of resistance training on preventing muscle atrophy and bone loss under simulated weightlessness, and identified moderating factors influencing these outcomes.MethodsPubMed, Web of Science, Scopus, and SPORTDiscus were searched for articles up to October 2024. Study quality was assessed with the PEDro scale, publication bias with funnel plots and Egger’s test, and certainty of evidence with the GRADE approach. A multilevel random-effects meta-analysis and moderator analyses were performed in R.ResultsEighteen studies (297 participants) were included. Resistance training significantly increased muscle cross-sectional area (CSA) with a large effect (g = 0.95, 95% CI: 0.50–1.39, p < 0.01), with the triceps surae showing the largest CSA gains (g = 2.29). Muscle volume also improved (g = 0.84, 95% CI: 0.57–1.12, p < 0.01), moderated by sex, training type, frequency, and muscle tested. Larger effects were seen in women (g = 2.33), concurrent training (g = 2.33), 2–3 weekly sessions (g = 2.33), and quadriceps (g = 1.62). Muscle strength increased substantially (g = 2.26, 95% CI: 1.42–3.11, p < 0.01), with greater gains in women (g = 3.49), concurrent training (g = 3.08), and 60–70 days of training (g = 2.92). For bone health, resistance training increased bone mineral content (g = 0.73, 95% CI: 0.41–1.05, p < 0.01) and bone formation markers (g = 0.69, 95% CI: 0.31–1.07, p < 0.01), but had no significant effect on bone resorption (g = 0.15, p > 0.01).ConclusionResistance training effectively attenuates muscle atrophy and improves strength, particularly in women, with concurrent training, moderate training frequencies, and 60–70 days programs. Benefits are most evident in the quadriceps and triceps surae. Resistance training also enhances bone mineral content and bone formation, though effects on bone resorption are negligible.